Motion detector alarm system / Mohammad Hakim Abu Bakar & Muhammad Syazwan Ariffuddin Mohd Kamaldin - Abu Bakar, Mohammad Hakim; Mohd Kamaldin, Muhammad Syazwan Ariffuddin (2015)
In Malaysia, almost every day we read about burglary cases reported in local newspapers. These cases have been one of the most serious problems that happen in our country, Malaysia. Not like in the past, burglars nowadays are too aggressive and brutal. Number of burglary cases increased as many people tend to get easy money to support their life expenses. To overcome this problem, people must do something to their houses. Based on the situation above, security system is one of the popular ways to guard our houses. Therefore the purpose of this project is to design and develop a home security system that can provide security against intrusion. The main component to develop the project is ARDUINO MEGA2560 board based on A Tmega2560 as microcontroller. The two detectors of PIR sensors and magnetic switch (magnetic contact sensor) are used as the input of the ARDUINO MEGA2560.